1979
DOI: 10.1073/pnas.76.3.1328
|View full text |Cite
|
Sign up to set email alerts
|

Large electrical currents traverse developing Ceropia follicles

Abstract: An intense (up to 20 M&A/cm2) steady electrical current enters the anterior or nurse cell end of the growing follicle (or oocyte-nurse cell complex) of the Cecropia moth and is balanced by a more diffuse current leaving elsewhere. In late growth stages, the total transfollicular current is about 100 nA. Moreover, a separate small current, of about 1 nA, seems to leave the furrow between the oocyte and the nurse cells. After the nurse cells collapse, but before shell formation, the transfollicular current is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Table 4 summarizes data showing that endogenous EM fields exist in a wide variety of developing systems and correlate with and predict spatio-temporal events in embryonic development. Developing systems generally drive steady ion currents and produce substantial fields within themselves; examples include currents that enter the prospective and continuing growth point of several tip growing plant cells, voltage across the cytoplasmic bridge between an insect oocyte and its nurse cell, current traversing a recently fertilized egg from animal to vegetal pole, and early potentials across embryonic Fields between egg-ovary systems drive materials into oocyte Hagiwara and Jaffe, 1979;Jaffe and Woodruff, 1979;Barish, 1983;Nuccitelli, 1983;Bohrmann et al, 1984;Kunkel, 1986Kunkel, , 1991Bowdan and Kunkel, 1990;Kindle et al, 1990;Diehl-Jones and Huebner, 1993;Anderson et al, 1994;Kunkel and Faszewski, 1995 Eggs drive currents around themselves Chambers and de Armendi, 1979;Robinson, 1979;Bohrmann et al, 1986a;Bowdan and Kunkel, 1990;Kindle et al, 1990;Coombs et al, 1992;Anderson et al, 1994;Kunkel and Smith, 1994;Kunkel and Faszewski, 1995;Faszewski and Kunkel, 2001 Mouse and chick embryos drive fields around themselves Burr and Hovland, 1937b;Kucera and de Ribaupierre, 1989;Hotary and Robinson, 1990;Keefe et al, 1995 Neural tube of amphibians generates large fields Nuccitelli, 1984;Hotary and Robinson, 1991 Plants drive a variety of fields which correlate with sites of growth and also predict growth rates and dimensions of final shape Burr, 1942Burr, , 1950…”
Section: Patterning Fields In Embryonic Developmentmentioning
confidence: 99%
“…Table 4 summarizes data showing that endogenous EM fields exist in a wide variety of developing systems and correlate with and predict spatio-temporal events in embryonic development. Developing systems generally drive steady ion currents and produce substantial fields within themselves; examples include currents that enter the prospective and continuing growth point of several tip growing plant cells, voltage across the cytoplasmic bridge between an insect oocyte and its nurse cell, current traversing a recently fertilized egg from animal to vegetal pole, and early potentials across embryonic Fields between egg-ovary systems drive materials into oocyte Hagiwara and Jaffe, 1979;Jaffe and Woodruff, 1979;Barish, 1983;Nuccitelli, 1983;Bohrmann et al, 1984;Kunkel, 1986Kunkel, , 1991Bowdan and Kunkel, 1990;Kindle et al, 1990;Diehl-Jones and Huebner, 1993;Anderson et al, 1994;Kunkel and Faszewski, 1995 Eggs drive currents around themselves Chambers and de Armendi, 1979;Robinson, 1979;Bohrmann et al, 1986a;Bowdan and Kunkel, 1990;Kindle et al, 1990;Coombs et al, 1992;Anderson et al, 1994;Kunkel and Smith, 1994;Kunkel and Faszewski, 1995;Faszewski and Kunkel, 2001 Mouse and chick embryos drive fields around themselves Burr and Hovland, 1937b;Kucera and de Ribaupierre, 1989;Hotary and Robinson, 1990;Keefe et al, 1995 Neural tube of amphibians generates large fields Nuccitelli, 1984;Hotary and Robinson, 1991 Plants drive a variety of fields which correlate with sites of growth and also predict growth rates and dimensions of final shape Burr, 1942Burr, , 1950…”
Section: Patterning Fields In Embryonic Developmentmentioning
confidence: 99%
“…In each of these insects intracellular electrodes revealed intercellular voltage gradients that correlated with the movement of the charged molecules. Use of the vibrating probe developed by Jaffe and Nuccitelli (1974) demonstrated that extracellular currents also occur around these follicles (for Hyalophora, Jaffe and Woodruff 1977;1979;Woodruff et al 1986b; for Dysdercus, Dittmann et al 1981; for Rhodnius, Huebner amd Sigurdson 1986), and also around the follicles of Sarcophaga bulatta, Locusta migratora (Verachtert and De Loof 1986), Periplaneta americana, Ips perturbatus, Sialis vulata (Huebner and Sigurdson 1986), Blattela germanica (Kunkel 1986), and Drosphila, (Bohrmann etal. 1984;1986a;Overall and Jaffe 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Only the most peripherally located follicle cells in the furrow between trophocyte and oocyte compartment show some labelling. With the vibrating probe technique, a strong outward ionic current has been measured at this site (Jaffe and Woodruff, 1979). Our results suggest that V-ATPase, detected by our antiserum, is not of prime importance for generating this current pattern.…”
Section: Discussionmentioning
confidence: 54%